2016
DOI: 10.1002/adma.201603174
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Mediated Selective Growth of MoS2/WS2 and WS2/MoS2 Vertical Stacks on Au Foils for Direct Photocatalytic Applications

Abstract: A growth-temperature-mediated two-step chemical vapor deposition strategy is designed to synthesize MoS /WS and WS /MoS stacks on Au foils. Predominantly A-A stacked MoS /WS and A-B stacked WS /MoS are selectively achieved and confirmed. Relative enhancements or reductions in photocatalytic activities of MoS /WS or WS /MoS are observed under illumination, because the type-II band alignment enables directional electron flow from electrode to active site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
140
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 200 publications
(144 citation statements)
references
References 43 publications
2
140
0
2
Order By: Relevance
“…From the material design perspective for an efficient visible-light-driven sensitized heterojunctional photocatalyst, the primary concern is that the hybrid narrow band gaps (1.1–1.7 eV) can closely match the solar spectrum [18]. In fact, the typical 2D layered semiconductors, such as MoS 2 or g-C 3 N 4 , have received significant attention to explore potential photocatalysis applications, which lead to TMD nanosheet which is often utilized as a supporter to establish the heterostructured composite photocatalysts via different energy band hybrid strategies [19, 20]. For instance, the hierarchical MoS 2 /Bi 2 MoO 6 composites exhibited an efficient performance for photocatalytic oxidation of rhodamine B under visible-light irradiation [21].…”
Section: Introductionmentioning
confidence: 99%
“…From the material design perspective for an efficient visible-light-driven sensitized heterojunctional photocatalyst, the primary concern is that the hybrid narrow band gaps (1.1–1.7 eV) can closely match the solar spectrum [18]. In fact, the typical 2D layered semiconductors, such as MoS 2 or g-C 3 N 4 , have received significant attention to explore potential photocatalysis applications, which lead to TMD nanosheet which is often utilized as a supporter to establish the heterostructured composite photocatalysts via different energy band hybrid strategies [19, 20]. For instance, the hierarchical MoS 2 /Bi 2 MoO 6 composites exhibited an efficient performance for photocatalytic oxidation of rhodamine B under visible-light irradiation [21].…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of graphene, 2D materials, such as tungsten disulfide (WS 2 ) and other transition metal dichalcogenides (TMDCs), have drawn a great deal of interest due to their attractive physical and electronic properties [1][2][3]. It is reported that the hydrogen binding energy of MoS 2 is close to that of Pt-group metals, thus hinting at potential applications of other TMDCs in photocatalytic HER [4][5][6][7][8][9]. Both computational and experimental results have confirmed that the photocatalytic activities of XS 2 (X could be other transition metals, such as W) mainly stem from the edges rather than the basal planes [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The former two growth systems can be readily used for the onsite STM/STS characterizations of the atomic‐scale structures, defects, and the related electronic properties . The direct electrocatalytic and photocatalytic measurements can also be conducted on Au foils or glass carbon electrode materials, thus providing straight evidences for their applications in related fields.…”
Section: Preparation Methods Of 2d Mtmdcsmentioning
confidence: 99%